The geography of despair in England and Wales: putting suicide on the map - Middleton, Nicos; Sterne, Jonathan A.C.; Gunnell, David J. (My University, 2006)
Background: In recent years there have been marked changes in the age patterning of suicide mortality in Britain as well as in much of the industrialised world.1 Due to the fact that the most unfavourable trends have generally been experienced by the young, suicide now ranks as one of the principal causes of premature mortality.2 For over a century, a striking feature of the epidemiology of suicide has been the wide geographical variation in its occurrence (more than 10-fold differences in rates across Europe).1 3 Differences of similar magnitude have been reported within Britain4 and even across smaller-areas within particular cities.5.The UK government has recently recognised suicide (and mental health) as an important contributor to area health inequalities; 6 however, the geography of suicide is not yet well understood. To date, studies in Britain, as well as abroad, have generally: (i) focused on relatively large areas – heterogeneous in terms of the socio-economic characteristics of the 66 communities that comprise them (largest 3000 areas in the US7 8), or smaller areas within a defined locality e.g. city or district,5 or (ii) have not investigated whether the geography of suicide varies across the different age-groups – as recent changes in its age-patterning might suggest, or (iii) with the exception of a series of studies in London,5 9 10 have commonly favoured simple regression approaches that treat geographical areas as independent.
Keywords: Suicide; England; Wales; Mortality